2021
DOI: 10.1111/jrh.12603
|View full text |Cite
|
Sign up to set email alerts
|

The role of race in rural‐urban suicide disparities

Abstract: Purpose To assess the role that race‐ethnicity plays in modifying the observed rural‐urban disparity in suicide among Veteran Health Administration (VHA) users. Methods We performed a retrospective cohort study of 10,737,864 VHA users between 2003 and 2017, using cross‐linked VHA medical records and National Death Index mortality data to assess longitudinal race‐stratified rural‐urban differences in age‐ and sex‐adjusted annual suicide rates. We used Poisson regression and generated incident rate ratios (IRRs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
8
2
Order By: Relevance
“…In conclusion, rural Hispanic VA patients have a higher suicide rate than urban Hispanic VA patients. This is in contrast to our prior findings in non‐Hispanic VA patients, where the rural‐urban disparity in suicide was more easily explained by rural‐urban differences in sex and race 7 . Individual mental health diagnoses were the most important predictors of suicide among rural Hispanic VA patients and the rate of these disorders is increasing.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In conclusion, rural Hispanic VA patients have a higher suicide rate than urban Hispanic VA patients. This is in contrast to our prior findings in non‐Hispanic VA patients, where the rural‐urban disparity in suicide was more easily explained by rural‐urban differences in sex and race 7 . Individual mental health diagnoses were the most important predictors of suicide among rural Hispanic VA patients and the rate of these disorders is increasing.…”
Section: Discussioncontrasting
confidence: 99%
“…We recently performed a series of national studies to better understand the drivers of the rural‐urban disparity in suicide mortality among patients of the US Department of Veterans Affairs (VA). We found that rural VA patients were more likely to be non‐Hispanic White and male than urban VA patients and that the concentration of demographic risk factors in rural settings drove the disparity 6,7 . Furthermore, we found that individual risk factors, such as race, sex, and mental health diagnoses, mattered far more than rural‐urban contextual differences in predicting death by suicide among VA patients 6,8 .…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations